2016
DOI: 10.1021/acs.jpca.6b00921
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Structures of Ru-Centered Dyes: A Computational Screening Tool

Abstract: Dye-sensitized solar cells (DSCs) represent a means for harvesting solar energy to produce electrical power. Though a number of light harvesting dyes are in use, the search continues for more efficient and effective compounds to make commercially viable DSCs a reality. Computational methods have been increasingly applied to understand the dyes currently in use and to aid in the search for improved light harvesting compounds. Semiempirical quantum chemistry methods have a well-deserved reputation for giving goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…To realize a complete screening methodology for transition metal dyes, it is necessary to be able to optimize candidate molecular structures and compute their UV/vis spectrum quickly, cheaply, and accurately. In a previous publication, we showed that geometries calculated using Ru basis set parameters optimized for the semiempirical PM6 Hamiltonian for Ru‐centered dye‐sensitized solar cell molecules were in good agreement with optimized DFT geometries. As mentioned in that article, the speed and accuracy of the PM6 method, particularly with optimized basis set parameters, makes it an excellent candidate for computational screening of the geometries of thousands of candidate dyes.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…To realize a complete screening methodology for transition metal dyes, it is necessary to be able to optimize candidate molecular structures and compute their UV/vis spectrum quickly, cheaply, and accurately. In a previous publication, we showed that geometries calculated using Ru basis set parameters optimized for the semiempirical PM6 Hamiltonian for Ru‐centered dye‐sensitized solar cell molecules were in good agreement with optimized DFT geometries. As mentioned in that article, the speed and accuracy of the PM6 method, particularly with optimized basis set parameters, makes it an excellent candidate for computational screening of the geometries of thousands of candidate dyes.…”
Section: Introductionmentioning
confidence: 55%
“…To optimize the Ru basis set for Ru‐DSC geometries, a testing set of 20 molecules that contains the 13 molecules listed above and identical to the set used in our previous paper, was used. From this set, a training set of 5 molecules (Ru(DQPl) 2 (DQPl = 1,3‐ bis (8‐quinolinyl)‐pyrrole), Ru(DQPNH 2 ) 2 , Ru(DQP) 2 , Ru(DQPzP) 2 , Ru(TPy) 2 ) was taken.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Semiempirical quantum mechanical (SQM) calculations 7,8 are considered as a likely alternative, and reparameterization and/or modifications make it possible to apply SQM methods to energy minimizations for metalcontaining complexes. 9,10 We proposed a reparameterization of PM6 11 (called rPM6) targeting for open-shell molecules including 3d transition metal complexes, and the rPM6 parameters for several basic elements (i.e., H, C, N, O, P, and S) are now available. 1214 The applications of UrPM6 to various organic (di)radicals demonstrated its superior performance in both the electronic and geometric structures.…”
mentioning
confidence: 99%